Determination of Carrying Capacity Estimates for an Ecotourism Site within the Mount Banahaw-San Cristobal Protected Landscape (MBSCPL), Philippines - Sarmiento Banjie G. (E3S Web of Conferences)
Ecotourism is characterized as sustainable and thoughtful exploration of the environment. Protected Areas (PAs) are increasingly significant as ecotourism destinations. These locations face risks from uninformed and unregulated visitors who can cause pollution (air, noise, water, etc.) and alterations to the natural ecosystem processes. A comprehensive ecotourism planning and management approach should identify an optimal threshold for ecotourism attraction usage while maintaining a healthy biophysical and social environment. While carrying capacity is crucial for visitor regulation, its application and practice are currently lacking in Taytay Falls which is a part of the MBSCPL or Mount Banahaw-San Cristobal Protected Landscape. The site is situated within the municipality of Majayjay in the province of Laguna, Philippines. This research assessed the value of Taytay Falls with the use of carrying capacity estimates for the improvement of ecotourism management.